The effect of directed photogenerated carrier separation on photocatalytic hydrogen production. (November 2017) - Si, Yuelei; Cao, Shuang; Wu, Zhijiao; Ji, Yinglu; Mi, Yang; Wu, Xiaochun; Liu, Xinfeng; Piao, Lingyu
Abstract: The one-dimensional metal-semiconductor hybrids with directed photogenerated carrier separation rather than random flow direction of photogenerated electrons and holes possess more advantages to achieve long-distance charge separation and efficient solar energy conversion efficiency. Here, we obtained the non-centrosymmetric Au /TiO2 nano-mushrooms (Au/TiO2 NMs) structures. The one-dimensional hybrid simultaneously maintains directed spatial charge separation properties and tunable light absorption. Owing to the well-designed structure, the H2 evolution rate can reach up to 52.6 μmol g −1 h −1 under sunlight irradiation from pure water without any sacrificial reagents. Based on the photocatalytic data, we can speculated that the directed spatial charge separation lead to the enhanced photocatalytic efficiency rather than the localized surface plasmon resonance (LSPR) effect of Au NRs. Besides, we confirmed the dominant electron transfer direction was from TiO2 NPs to Au NRs under sunlight irradiation. Graphical abstract: Highlights: Non-centrosymmetric one-dimensional Au /TiO2 nano-mushrooms were constructed. Directed spatial charge separation property was achieved. An enhanced H2 -production efficiency was obtained without any sacrificial reagents. The dominant electron transfer direction under sunlight irradiation was analyzed.